2010
DOI: 10.1186/cc9210
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective agreement and consent to neurocritical care is influenced by functional outcome

Abstract: IntroductionOnly limited data are available on consent and satisfaction of patients receiving specialized neurocritical care. In this study we (i) analyzed the extent of retrospective consent to neurocritical care--given by patients or their relatives--depending on functional outcome one year after hospital stay, and (ii) identified predisposing factors for retrospective agreement to neurocritical care.MethodsWe investigated 704 consecutive patients admitted to a nonsurgical neurocritical care unit over a peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
0
21
0
1
Order By: Relevance
“…However, functional outcome was poor especially in older patients with either hemorrhagic stroke or need of MV, leaving barely all survivors in a dependent state. Several studies have shown that retrospective consent to neurointensive care depends on the functional outcome [36,37] . In a cohort of 704 patients admitted to a neurocritical care unit, only 19% of patients with an outcome mRS of 4 or 5 retrospectively consented to ICU management [36] .…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…However, functional outcome was poor especially in older patients with either hemorrhagic stroke or need of MV, leaving barely all survivors in a dependent state. Several studies have shown that retrospective consent to neurointensive care depends on the functional outcome [36,37] . In a cohort of 704 patients admitted to a neurocritical care unit, only 19% of patients with an outcome mRS of 4 or 5 retrospectively consented to ICU management [36] .…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…Several studies have shown that retrospective consent to neurointensive care depends on the functional outcome [36,37] . In a cohort of 704 patients admitted to a neurocritical care unit, only 19% of patients with an outcome mRS of 4 or 5 retrospectively consented to ICU management [36] . Further decisions about when to admit stroke patients to ICU will thus have to focus on the potential functional outcome, taking account of accepted predictors of poor outcome.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…Given that only ICHs with a volume 1 20 cm 3 were included in the study, functional outcomes were classified into favorable (mRS 0-2), acceptable (mRS 0-4) and unfavorable (mRS 5-6) outcomes. The cut-off point between acceptable and unfavorable outcomes was chosen according to the results of studies evaluating the opinions of the patients and their relatives on acceptable outcomes in a comparable intensive-care patient cohort [19,20] .…”
Section: Outcome Assessmentmentioning
confidence: 99%
“…35 Stroke survivors who have received aggressive life-prolonging neurointensive care have generally high rates of perceived satisfaction with quality of life, even as a significant percentage of the patients with worse functional outcomes in retrospect would have refused the care when offered. 36 Accuracy of prognosis is also a concern here; an older metaanalysis looking at outcomes and early prognosis in mechanically ventilated patients with both ischemic and hemorrhagic subtypes found less functional disability than predicted in the subset of patients who survived the initial 30 days after hospitalization. 37 The preceding concerns about prognostication, whether using various objective scales or a more subjective holistic view of the patient's clinical situation, are not intended to suggest that limiting treatment is inappropriate in all cases or that paternalistic application of principles of beneficence and nonmaleficence demands aggressive intervention in all patients regardless of their wishes.…”
Section: Prognostication Mortality and Limitations On Carementioning
confidence: 99%